Bureaucratic Ethics and the Actualization of Pancasila Values in Public Service Delivery: A Convergent Mixed-Methods Study of a Local Government Institution in Indonesia - Indrayani; Henry Halim; Machdaliza; Aziwarti; Martimbang Simbolon (HM Publisher, 2024)
Public administration in Indonesia is constitutionally bound by the ethical principles of Pancasila, yet systemic bureaucratic pathologies frequently contradict these ideals; limited research has quantified how each value is actualized in frontline service. This convergent parallel mixed-methods study examined the actualization of Pancasila values in public service delivery at a local government institution in Indonesia and its association with perceived public service quality. A qualitative strand (in-depth interviews with bureaucrats, n = 6, and service users, n = 10, participant observation and document analysis) was integrated with a cross-sectional survey of 216 service users and civil servants using six validated multi-item scales (Cronbach's alpha 0.78-0.93). Data were analyzed with Pearson correlation, multiple linear regression, Welch's t-test and one-way ANOVA, reporting effect sizes and 95% confidence intervals. Social cohesion (Sila 3, mean 3.96) and the local Malay ethos (4.07) were strongly actualized, whereas transparency (Sila 4, 2.85), integrity (Sila 1, 3.01) and distributive justice/access (Sila 5, 2.74) were deficient. Transparency (beta = 0.302, 95% CI 0.167-0.345, p < 0.001) and integrity (beta = 0.280, 95% CI 0.146-0.326, p < 0.001) were the strongest predictors of service quality, with the model explaining 60.5% of variance (F(6,209) = 53.41, p < 0.001). Service accessibility declined sharply from urban to rural respondents (d = 0.628; ANOVA eta-squared = 0.147, p < 0.001). Actualizing Pancasila requires structural integrity and transparency reform anchored in local cultural paradigms; a Socio-Cultural Public Service Model is proposed.